Investment by private land developer companies and postcolonial urban growth in Ruwa (Zimbabwe), 1986-2015 - Terence Muzorewa; Terence Muzorewa; Mark Nyandoro; Mark Nyandoro (University of the Free State, 2023)
This article qualitatively analyses the role of private land developer companies’ investment in postcolonial Zimbabwe’s urban development, with special reference to Ruwa Town. This sprawling town is outstanding for involving private land developers in its growth and expansion. All postcolonial established towns had emerged out of Government’s direct investment through the Growth Point policy. By contrast, Ruwa was peculiar, because it developed from a public-private partnership approach. The article argues that, in the absence of State financial capacity in the postcolonial era, developer companies played a crucial role in infrastructure development and facilitation of public amenities. Although the companies were important in spearheading the growth of the town, they sometimes failed to meet certain standards of quality in urban infrastructure development required by town planning authorities. Despite this shortcoming, the article finds that the companies were essentially the most appropriate vehicles of urban development in times of economic crisis in the country.